PHYTOCHEMISTRY, CYTOTOXIC AND ANTIMICROBIAL ACTIVITIES OF SECONDARY METABOLITES FROM TREE BARKS AND ROOT CULTURES OF Morus macroura Miq. (ANDALAS) - Jasmansyah
Morus plants, or known as “Mullbery”, consist of about 28 species and one of economically important genus in the family Moraceae. The distribution of this genus covers the tropical and subtropical regions of Asia, Europe, North America, South America, and Africa. This group of plants has an important relationship with silk industries because Morus leaves are used to feed silkworm?s. In addition to that, the fruits of Morus are edible, while its woods are a good source for home construction and furnitures. One of Morus species endemic to Indonesia is Morus macroura Miq. This species endemically growth in the west part of Sumatera, and is locally known as “Andalas”. Beside in this region, M. macroura can also be found in the southern part of China.